The Effect of Humors and Narcissistic Personality on The Innovative Output with Innovative Work Behavior and Adaptability as Variables of Mediation - Kusumawardani, Dian; Wulansari, Nury Ariani (Management Analysis Journal, 2018)
This research aims to know the role of innovative work behavior mediation and adaptability on the relationship of humor and narcissistic personality on the innovative output. The population in this study was all owners of SME in the Semarang city. The data collection method were observation, interview, and questioners. The sampling technique was multiple random sampling. The sample size was 201 SME actors. Methods of data analysis applied in this research were descriptive analysis, validity and reliability test, and hypothesis test. The data analysis was done by using WarpPLS software version 6.0. The results showed that humor and narcissistic personality increases innovative work behavior, adaptability and innovative output. In addition, innovative work behavior and adaptability also had a positive and significant influence on innovative output. Furthermore, this research found that the effect of humor and narcissistic personality on innovative output can be mediated by innovative work behavior and adaptability.